The influence of different preparation methods on the erosion behavior of NiP-ZrO2 nanocomposite coating - Mostafa H. Sliem (6316958) (2023)
Three different deposition techniques were utilized to synthesize NiP-ZrO2 nanocomposite coatings. The structural and mechanical merits for the as-prepared coatings were compared through XRD, XRF, SEM, AFM, microhardness, and nanoindentation analysis. The pulse-electrodeposition was the most suitable technique with a hardness value of 653HV25. The erosion behavior for the different NiP-ZrO2 coatings was investigated based on erosion duration, particles velocity, and impact angle. The results shows that the erosion rate decreases linearly with increasing angle of incidence and increases with increasing particle velocity. The erosion mechanism is mainly fracturing of splats and ploughing action at low particle velocity due to the ductility merits of the different coatings. In contrast, larger craters, radial cracks, and micro cuttings were observed at higher speeds. Other Information Published in: Tribology International License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.triboint.2022.108014